Effectiveness of Simulation Techniques on the Nursing Students Knowledge toward Cardiopulmonary Resuscitation for Adults at College of Nursing/University of Baghdad - Musaab Majid Abdulwahhab (Kufa Journal for Nursing Sciences)
Objectives: The study aims to find out the effectiveness of simulation on the students knowledge toward Cardiopulmonary resuscitation for adults